Some recent developments on functional data analysis* - Cugliari Jairo; Devijver Emilie; Meynaoui Anouar; Mignot Raphaël (ESAIM: Proceedings and Surveys)
Recent contributions to functional data analysis are presented. Various problems are considered including the definition of the barycenter of multivariate functional data and the adaptive nonparametric estimation in the functional linear model with functional output.